Development of Egg Hatching and Storage Machines Equipped with Cooling and Heating Systems and IoT - Yunus, Faizal Amin Nur; Hussin, Muhammad Nur Aizat Hussin; Rahim, Mohd Bekri; Razali, Nizamuddin; Rozali, Mohd. Zulfadli; Abdul Rahman, Khairul Anuar (Research and Innovation in Technical and Vocational Education and Training, 2021)
The development of egg hatching and storage machines in combination with cooling and heating systems along with the IoT was developed to help chicken breeders address the issue of chicken production shortages. To produce large numbers of poultry production, breeders need a hen to produce eggs. A young hen ignores eggs in the early stages. Plus, eggs without a hen take care of will be eaten by the rooster. Threats to eggs can also reduce the production of poultry. In addition, if the eggs are not incubated within 1 week, the eggs will be damaged. Having a hatching machine and egg storage can help the chicken breeders to produce a better amount of chicken production. Internet of Things (IoT) elements such as the Arduino and Blynk are also used to make this egg hatching and storage machine attractive and to meet the needs and requirements of users. The objectives of this study were to design, develop and evaluate the functionality of egg hatching and storage machines in combination with cooling and heating systems along with IoT. Methodology is a technique and method that incorporates methods and approaches used to achieve the objectives and objectives of the study. The model used is the ADDIE model which consists of 5 phases namely Analysis, Design, Development, Implementation, and Evaluation. This product has received expert confirmation in terms of design and functionality. The results show that the egg hatching and storage machine is well developed and can attract users when using this hatching and storage machine.